The Need Of Incorporating CIDOS With Facebook To Facilitate Online Collaborative Learning - Sharifah Nadiyah, Razali; Faaizah , Shahbodin; Norasiken , Bakar; Hanipah , Hussin; Mohd Hafiez, Ahmad (WITPress, 2013)

(untitled)
Getting a job after completing college is always a challenge for students; even though they acquired an excellent academic skill. Therefore, the role f Higher Education Institutions is to provide training to the students with the soft skills in accordance with the demands of the job. Collaborative learning has been well known in the educational arena with proven results in terms of developing soft skills. This study aims to explore the need of incorporating Moodle with Social Network Sites to facilitate online collaborative learning. In order to obtain data for this preliminary study, two sets of questionnaire were personally distributed to 356 diploma students and 145 lecturers from Politeknik Ibrahim Sultan, Politeknik Merlimau, Politeknik Tuanku Syed Sirajuddin, Politeknik Kota Kinabalu and Politeknik Sultan Idris Shah. All collected data had been analyzed using SPPS 19 software and the results of the study showed lecturers have to apply certain instrument to record and monitor students discussion and to asses student contribution from the discussion. But most lecturers and students tend to access their Social Network Sites account daily compares to CIDOS. Incorporating CIDOS with Facebook to support online collaborative learning as recommendations for future research is suggested.